Differences in plaque index among children aged 6-12 years before and after acquiring a toothbrushing before bedtime habit - Simanjuntak, Debora Rotua Novita; Gartika, Meirina; Setiawan, Arlette Suzy Puspa Pertiwi (Padjadjaran Journal of Dentistry, 2015)
Introduction: The habit of brushing teeth before bedtime is very important to keep the teeth and mouth clean and healthy this can be evaluated from the plaque index. The objective of this study was to analyzed differences of plaque index among children aged 6-12 years old in Panti Sosial Asuhan Anak William Booth and Rumah Perlindungan Sosial Asuhan Anak (RPSAA) Ciumbuleuit Bandung before and after acquiring a habit of brushing their teeth before bedtime. Methods: This study was a quasi-experimental and it was analyzed statistically using the t test. Total subjects of 31 children consist of 22 children in Panti Sosial Asuhan Anak William Booth and 9 children in Rumah Perlindungan Sosial Asuhan Anak (RPSAA) Ciumbuleuit Bandung. Data was obtained through clinical examination with the PHP (Personal Hygiene Performance) plaque index of Podshadley and Haley. Results: The mean plaque index before acquiring a habit of brushing teeth before bedtime is 2.247 and after, is 0.591. Conclusion: There is a difference in plaque index in children aged 6-12 years in Children's Orphanage William Booth and RPSAA Ciumbuleuit Bandung before and after acquiring a habit of brushing before bedtime.